Ophthalmic, clinical and visual electrophysiological findings in children born to mothers prescribed substitute methadone in pregnancy. Issue 6 (21st April 2010) - Hamilton, R; McGlone, L; MacKinnon, J R; Russell, H C; Bradnam, M S; Mactier, H
Abstract : Background and aims: There are growing concerns regarding visual outcome of infants exposed to opiates (including substitute methadone) and/or benzodiazepines in utero. We describe the combined ophthalmology and visual electrophysiology findings in 20 infants and children who had been exposed to substitute methadone and other drugs of misuse in utero. Methods: This was a descriptive case series of 20 patients, all of whom had been referred to a paediatric visual electrophysiology service because of concerns regarding visual function, and all of whom had been exposed to methadone in utero. All children underwent a full ophthalmic and orthoptic examination as well as visual electrophysiology testing deemed appropriate on an individual basis. A review was undertaken of paediatric case notes and of maternal antenatal urine toxicology. Results: Ophthalmic abnormalities included reduced acuity (95%), nystagmus (70%), delayed visual maturation (50%), strabismus (30%), refractive errors (30%), and cerebral visual impairment (25%). Visual electrophysiology was abnormal in 60%. A quarter of the children had associated neurodevelopmental abnormalities. The majority of children with nystagmus (79%) had been treated for neonatal abstinence syndrome (NAS). Conclusion: Infants born to drug-misusing mothers prescribed methadone in pregnancy are at risk of a range of visual problems, the underlying causes of which are not clear. Those infants with NAS severe enough to receive pharmaceutical treatment may be at particular risk of developing nystagmus. The inclusion of visual electrophysiology in comprehensive visual assessment of children exposed to substance misuse in utero may help clarify the underlying causes by differentiating abnormalities of retinal and cortical origin.